Breaking the cycle of intergenerational childhood maltreatment: effects on offspring mental health - Islam, Samiha (Child maltreatment, 2023)
This study evaluated how continuities and discontinuities in the intergenerational transmission of maltreatment affect offspring psychopathology. Data from a multigenerational prospective, longitudinal study were used to compare the severity of offspring psychopathology in families with no history of maltreatment (controls) and those in which parents, offspring, or both experienced childhood maltreatment (cycle breakers, initiators, and maintainers, respectively). Participants included 454 parents (Mage = 47.1, SDage = 3.4) and their 697 offspring (Mage = 22.3, SDage = 6.3). Offspring of cycle breakers reported less psychopathology than offspring of cycle maintainers and did not report more psychopathology than offspring of controls. Offspring of cycle initiators and maintainers reported comparable levels of psychopathology. Results suggest that breaking the cycle of maltreatment buffers offspring from risk for psychopathology associated with parental maltreatment, with no enduring or additive effects of maltreatment across generations. Our findings highlight the need for maltreatment prevention programs and further research to identify conditions and characteristics that reduce the probability of intergenerational transmission.